농촌 노인과 도시 노인의 체력 수준 비교분석 - 성순창; 김현수; 이만균 (Exercise science (Seoul, Korea), 2011)
본 연구의 목적은 농촌 노인과 도시 노인의 일상생활체력을 비교하는 것이다. 농촌거주 농업종사 노인 394명과 도시거주 노인 627명을 다단계층화 집락 무선추출법으로 선정하였다. 3개의 체격검사 항목과 7개의 체력 검사항목(성순창 등, 2004; Rikli & Jones, 2001)으로 체격과 체력을 측정한 후, 그 결과를 두 집단 간에 전체와 연령대 별로 구분하여 비교하였다. 도시 노인에 비하여 1) 남자의 눈뜨고외발서기와 여자의 등뒤에서손잡기를 제외한 모든 항목에서 농촌 노인이 도시 노인에 비하여 더 우수하였다. 2) 남자의 연령대별 비교 결과, 체지방률 (모든 연령대 집단), 좌․우 악력 (65∼69세), 아령들기 (70∼74세, 75∼79세), 의자앉았다일어서기 (70∼74세, 80세 이상), 등뒤에서손잡기 (75∼79세, 80세 이상), 의자앉아윗몸앞으로굽히기 (65∼69세, 70∼74세, 80세 이상), 그리고 2.44m 왕복걷기 (65∼69세, 70∼74세, 75∼79세)에서 농촌 노인이 도시 노인에 비하여 더 우수하였다. 3) 여자의 연령대별 비교 결과, 체지방률 (모든 연령대 집단), 좌․우 악력 (65∼69세, 70∼74세), 아령들기 (모든 연령대 집단), 의자앉았다일어서기 (70∼74세), 등뒤에서손잡기 (65∼69세, 70∼74세), 의자앉아윗몸앞으로굽히기 (75∼79세, 80세 이상), 눈뜨고외발서기 (70∼74세), 그리고 2.44m 왕복걷기 (80세 이상)에서 농촌 노인이 도시 노인에 비하여 더 우수하였다. 결론적으로, 농촌 노인의 체력이 도시 노인보다 우수한 것으로 나타났다. 향후 농촌 노인과 도시 노인 간에 체력의 차이가 나타나는 원인을 분석하기 위하여 농촌과 도시 노인의 생활 습관과 환경을 동시에 조사하는 연구가 요청된다. The purpose of this study was to compare daily living fitness levels between elderly farmers and urban dwellers. Three hundreds-ninety-four farmers and six hundreds-twenty-seven urban dwellers were selected as subjects by multi-stage stratified cluster random sampling. Seven physical fitness test items were selected based on the suggestion by Rikli and Jones (2001). 1) Physical fitness levels of the farmers were significantly better than urban dwellers except one leg standing with eye-open for males and back scratch test for females. 2) For males, percent body fat (all age groups), grip strength (65-69 yrs), arm curl (70-74 & 75-79 yrs), chair stand (70-74 yrs, over 80 yrs), back scratch test (75-79 yrs, over 80 yrs), sit-and-reach (65-69 yrs, 70-74 yrs, over 80 yrs), and 2.44m up-and-go (65-69 yrs, 70-74 yrs, 75-79 yrs) of farmers were significantly better than urban dwellers. 3) For females, percent body fat (all age groups), grip strength (65-69 yrs, 70-74 yrs), arm curl (all age groups), chair stand (70-74 yrs), back scratch test (65-69 yrs, 70-74 yrs), sit-and-reach (75-79 yrs, over 80 yrs), one leg standing with eye-open (70-74 yrs), and 2.44m up-and-go (over 80 yrs) of farmers were significantly better than urban dwellers. It was concluded that physical fitness level of the farmers was better than urban dwellers. Research elucidating the reasons for the difference between two districts by investigating the life patterns and environment would be warranted in near future. KCI Citation Count: 15